Evaluation of emergency contraception use among women receiving gynecological treatment in the Brazilian Amazon - Priante, Paulo Sérgio Barbalho; Lubianca, Jaqueline Neves; Cioba, Christine; Corleta, Helena von Eye; Capp, Edison (Clinical and Biomedical Research, 2014)
Introduction: The use of a postcoital hormonal contraception regimen has been described and is known as emergency contraception (EC) or “the morning-after pill”. The aim of this study was to evaluate the use and level of knowledge about emergency oral contraception (EC) among women attending the gynecology outpatient clinic of the Hospital Fundação Santa Casa de Misericórdia of the State ofPará, the second largest state in the Brazilian Amazon. Methods: a cross-sectional study was conducted with 316 sexually active women, aged 18 to 50 years, who attended the gynecology outpatient clinic. Participants were included based on spontaneous demand between June and July 2012. Patients answered a questionnaire with 29 questions, including: age in years, educational attainment, knowledge about EC, and previous use of the method. The primary outcome was knowledge on EC use. Results: Participants’ mean age was 31.84 years (SD ± 8.00). As for their educational level, 46.84% of them had completed high school, and only 8.55% had higher education. Most of the women obtained information about EC through friends (48.61%, n = 152), and only 7.30% from their doctors. Although most participants (83.54%) reported to be aware of the method, only 0.63% reported that EC could be used up to 5 days after unprotected intercourse; 57.59% did not know how to use it; and 76.58% (n = 242) had never used the method. Conclusion: The women in our study seem to have a high level of knowledge and prevalence of use of emergency contraception, although few of them knew about the time limit for its use. They should receive more information about emergency contraception.